Association between Chinese visceral adiposity index and lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH): a national cohort study - Kunhui Chang; Bo Li; Gang Wang; Hao Zhou; Yonghao Chen; Hongbing Gu (BMC Urology)
Abstract Background Benign prostatic hyperplasia (BPH) and its related lower urinary tract symptoms (LUTS) are commonly observed among aging males and have a substantial effect on quality of life. Metabolic syndrome, with a specific focus on obesity, is believed to play a role in the development of BPH. This study intends to explore the relationship between several obesity-related metrics, including the Chinese Visceral Adiposity Index (CVAI), and LUTS/BPH within a national cohort of Chinese men. Methods Data from the China Health and Retirement Longitudinal Study (CHARLS) 2015 were analyzed, encompassing a sample of 5,735 male participants aged 45 and older. Eight obesity-related indices—namely Body mass index (BMI), Waist-height ratio (WHtR), Triglyceride-glucose.BMI (TyG.BMI), TyG. Waist circumference (TyG.WC), TyG.WHtR, CVAI, Visceral adiposity index (VAI), and A body shape index (ABSI)—were examined. Logistic regression models, adjusted for potential confounders, were utilized to evaluate the associations between these indices and LUTS or BPH. The predictive capabilities of these indices were further assessed using receiver operating curves (ROC). Results Among the participants, 718 (12.5%) were diagnosed with LUTS/BPH. All obesity-related indices were significantly higher in the LUTS/BPH group compared to the healthy group. CVAI demonstrated the highest predictive ability for LUTS/BPH, with an area under the curve (AUC) of 0.58. The study highlighted a nonlinear relationship between LUTS/BPH and several obesity-related indices, including CVAI. Conclusions This study underscores the significant association between visceral fat, as measured by CVAI, and the risk of LUTS/BPH in Chinese men. CVAI emerged as the most effective predictor among the indices evaluated, suggesting its potential utility in identifying individuals at risk for LUTS/BPH. Further prospective studies are needed to confirm these findings and elucidate the underlying mechanisms.